PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN KEMAMPUAN KONEKSI MATEMATIKA SISWA SEKOLAH MENENGAH PERTAMA - Noviyanti, Noviyanti (Universitas Muhammadiyah Bengkulu, 2016)
This study aims to determine: (1) How does the use of contextual learning approach to creative thinking ability of students? (2) How does the use of contextual learning approach to mathematics connection ability of students? (3) How different the influence of contextual learning approach with conventional learning on students' ability to think creatively? (4) How do the differences influence of contextual learning approach with conventional learning on mathematics connection ability of students? This research is quantitative research with experimental methods in the form of pure experimental types. The population in this study were all eighth grade students of SMP Negeri 3 Lubuklinggau South Sumatra Province. The number of samples to be used in this research in experimental class 28 and class 29 controls. This study is a pure experiment using a pretest-posttest control group. In this study, the data collection method used is the technique of testing. From the analysis it can be concluded that: (1) There is a significant influence of contextual learning on students' ability to think creatively mathematics. (2) There is a significant influence of contextual learning on mathematics connection ability of students. (3) There is a significant difference in the effect of contextual learning with conventional learning on students' ability to think creatively mathematics. (4) There is a significant difference in the effect of contextual learning with conventional learning on mathematics connection ability of students. From this research, the authors recommend the need for an alternative approach to the selection of appropriate learning to improve the ability of creative thinking and the ability to connect mathematics to be applied, also the importance of pretest and posttest during the process of learning mathematics.Â KeywordsÂ Â : Contextual, Creative Thinking Mathematics, Mathematical Connections